Sanguinarine Reverses Pulmonary Vascular Remolding of Hypoxia-Induced PH via Survivin/HIF1α-Attenuating Kv Channels - Fan, Fenling; Zou, Yifan; Wang, Yousen; Zhang, Peng; Wang, Xiaoyu; Dart, Anthony M.; Zou, Yuliang (Frontiers in Pharmacology, 2021)
Background: Similarities in the biology of pulmonary hypertension and cancer suggest that anti-cancer therapies, such sanguinarine, may also be effective in treating pulmonary hypertension. This, along with underlying biochemical pathways is investigated in this study. Methods: Rats were subjected to 4 weeks hypoxia (or control) with or without treatment with Sanguinarine. In addition pulmonary artery smooth muscle cells (PASMCs) were examined after 24-48 hour hypoxia (with normoxic controls) and with or without Sanguinirine Pulmonary artery pressures and plasma survivin levels were measured in vivo. Ex vivo tissues was examined histologically with appropriate staining. mRNA and protein levels of Survivin, HIF-1α , TGFb1, BMPR2, Smad3, P53 and Kv 1.2,1.5, 2.1 in PASMCs were determined by real-time PCR and Western blot in PASMCs and distal PAs tissue. PASMCs proliferation and changes of TGFb1 and pSmad3 induced by Sanguinarine were studied using MTT and Western blot. Electrophysiology for Kv functions were measured by patch-clamp experiments. Results： 4 weeks hypoxia resulted in increase in serum survivin and HIF1a, pulmonary artery pressures and pulmonary vascular remodeling.with hypertrophy. These changes were all decreased by treatment with sanguinarine. Hypoxia induced a rise of proliferation in PASMCs which was prevented by sanguinarine treatment. Hypoxic PASMCs had elevated TGFb1, pSmad3, BMPR2, HIF1a too. These increases were all ameliorated by sanguinarine treatment as well. Hypoxia treatment resulted in reduced expression and function of Kv 1.2,1.5, 2.1 channels and these changes were also modulated by sanguinarine. Conclusion Sanguinarine is effective in modulating hypoxic pulmonary vascular hypertrophy via the survivin pathway and Kv channels.